PENGARUH KELAS EDUKASI MP-ASI 4 BINTANG TERHADAP ASUPAN PROTEIN DAN KERAGAMAN PANGAN PADA BALITA USIA 6-59 BULAN - Delima Citra Dewi Gunawan; Vio Nita; Novi Indrayan; Farida Arintasari; Septriana Septriana; Intan Ariani (Medika Respati : Jurnal Ilmiah Kesehatan, 2022)
Background : Nutrition education is a process that can influence people's decisions to improve a child's diet, a balanced diet and diet to meet adequate intake according to a child's need. Objective: To determine effect of education class about 4 star MP-ASI on protein intake and food diversity. Methods : Quasi experiment research design with a pre-post test two group design. The research location in Bokoharjo village, with the number of respondents are 15 children in each group. Data analysis was used the McNemar test. Results : Typical protein intake prior to education in both groups were 80% good and 20% sufficient category. After intervention, protein intake in control groups is 80% more and 20% sufficient. Whereas the case group is 93.3% over and 6.7% sufficient. Food diversity before the education given to kontrol groups was 80% in a good and 20% in sufficient category. Whereas the case group is 53.3% good and 46.7% sufficient. After education,food diversity in the control group was 66.7%in a good and 33.3% in sufficient category. Whereas the case group was 80% good and 20% sufficient category. Protein intake in control groups  p-value= 0.453 and for control groups has p-value= 0.063. Food diversity in control groups acquired p-value= 0.625 and for case groups p-value= 0.019. Conclusion : There was an effect of education class about 4 star MP-ASI on food diversity but not on protein intake. Keywords: Education class; Protein intake; Food diversity.